Impulsowe układy transformujące napięcia przemienne - Fedyczak, Zbigniew (Zielona Góra: Oficyna Uniwersytetu Zielonogórskiego)
This monograph deals with PWM AC transforming circuits with electrical and hybrid (electrical and electromagnetic) coupling. There are utilized to change of physical quantity parameters relevant to AC electrical energy (load voltage, current and power) without change of the voltage fundamental harmonic frequency. Similarly, like in case of AC transformation by means of the conventional transformer.
Keywords: prądy zmienne; przekształtniki; topologie sterowników matrycowych (SM) prądu przemiennego; topologie sterowników matrycowo-reaktancyjnych (SMR) prądu przemiennego; metoda uśrednionych zmiennych stanu; uśrednianie bieżące; model uśredniony; funkcje układowe SM; właściwości układów z SM lub SMR; zastosowania układów z SM lub SMR; AC matrix-controller (MC) topologies; AC matrix-reactance controller (MRC) topologies; averaged state space method; running averaging; averaged model; circuit averaged model; MC and MRC circuit functions; circuits with MC or MRC properties; applications of circuits with MC or MRC